Survival and Biomass Production of Salvadora persica on Various Types of Salt Affected Soils under Arid Conditions in Rajasthan and Gujarat - Arya, Ranjana; Lohara, R R; Meena, R L (Annals of Arid Zone, 2016)
Salvadora persica (L), popularly known as miswak, toothbrush tree or khara jal, is facultative halophyte tree species growing on arid salt affected lands in Rajasthan, Gujarat, Punjab, Haryana and western Uttar Pradesh. Despite its multifold uses it is not very popular in afforestation program. Its slow growing nature may be the reason. Field trials were laid in arid sandy salt affected soils in Kaparda and Gangani in Jodhpur, Rajasthan, and highly saline black silty clay soils in little Rann of Kachchh, Patan Gujarat. It had very high survival rate at all the sites with appreciable biomass production. The survival was above 90% at Kaparda with slow growth, 85.2 to 66.7% survival and 7 to 12 kg plant-1 biomass yield with the use of FYM, gypsum and nitrogen on sandy soil, Gangani, Jodhpur at 72 months and 97.5 to 97.9% survival and 2.6 to 7.17 kg plant-1 biomass yield with FYM, wheat husk and nitrogen on silty black salty soil, Kordha Patan at 50 months. Thus, it can be concluded that with slight management S. persica is the best plant for various types of salt affected soils. Plantation of this important tree species will not only rehabilitate these wastelands, but also provide valuable products for livelihood support. Key words: Salvadora persica, FYM, gypsum, nitrogen, wheat husk, growth.